PENGARUH MULTIMEDIA COMPAIGN AKRONIM FAST (SEGERA) TERHADAP PENGETAHUAN KEGAWATDARURATAN PENYAKIT STROKE PADA MASYARAKAT DI DESA ROHMONI KEC. PULAU HARUKU - Umasugi, Muhammad Taufan (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Stroke is a major health problem in the community because it causes disability and decreased quality of life which has characteristic neurological signs and symptoms that develop rapidly, with symptoms lasting 24 hours or more and can even lead to death. However, the lack of knowledge of the Indonesian people about the signs and symptoms of stroke is a problem in stroke services in Indonesia due to low awareness and not optimal services in recognizing stroke symptoms that can worsen in minutes, hours and days. To find out and detect the occurrence of stroke, we can use the FAST method. This study aims to determine the effect of the Campaign Acronym Multimedia Fast (SeGeRa) on knowledge of the emergency of stroke in the community in Rohmoni Village, Kec. Haruku Island. The type of research used is quantitative research using a one-group pre-post test approach. The data analysis used was univariate and bivariate (Wilcoxon test). The sampling technique used is probability sampling with the type of simple random sampling. Communities that can be used as samples in this study are 90.90. The calculation results can be rounded up to 91 people. Data was collected using a questionnaire consisting of 20 knowledge questionnaires. The results of the study from the bivariate analysis showed p-value = 0.000